Cytogenetic findings in acute leukaemias of infants. - Lampert, F. (Nature Publishing Group, 1992)
Of 706 children, 528 with acute lymphoblastic leukaemia (ALL) and 178 with acute myelocytic leukaemia (AML), whose leukaemia karyotypes could be successfully analysed, 48 were infants less than 1 year of age, 28 with ALL (5% of ALL patients) and 20 with AML (11% of AML patients). In contrast to older children. ALL-leukaemocytogenetics in infants was characterised by lack of hyperdiploidy with over 50 chromosomes and higher incidence of pseudodiploidy. Thirteen (= 46%) infants had an 11q23 aberration, and 11 of them had t(4;11). In AML, nine (= 45%) infants also had an 11q23 abnormality, e.g. t(9;11). Thus, the 11q23 aberration was present in almost 50% of all leukaemia karyotypes of infants. In ALL of infants, the CALLA negative, pre-pre-B immunophenotype prevailed. In AML of infants, the monocytic subtype dominated. A biphenotypic morphology (lymphoid-monocytic) with the expression of lymphoid and myeloid antigens was seen in several ALL and AML cases. In conclusion, leukaemogenesis in infants is a rare event, arising in stem cells of very early hematopoietic differentiation (probably due to gene rearrangement errors, most frequently at FRA11B), and differs from leukaemogenesis in older age groups by unique clinical and cellular features.